2010
DOI: 10.1016/j.ejcts.2009.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma and thymic carcinoma

Abstract: Thymoma and thymic carcinoma are an extremely heterogeneous group of neoplastic lesions with an exceedingly wide spectrum of morphologic appearances. They show different presentations with a variable and unpredictable evolution ranging from an indolent non-invasive attitude to a highly infiltrative and metastasising one. Prognosis can be predicted on the basis of a number of variables, mainly staging, the WHO histological pattern and diameter of the tumour. Complete surgical resection is certainly the gold sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 191 publications
(283 reference statements)
4
156
0
16
Order By: Relevance
“…Thymic carcinoma is exceedingly rare, accounting for less than 10-20 % of all thymic tumors [10,15]. Although MG is not commonly observed in patients with thymic carcinoma, it can still be considered as a paraneoplastic Although the underlying mechanisms that link MG to a better prognosis are unclear, the following theories may contribute.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thymic carcinoma is exceedingly rare, accounting for less than 10-20 % of all thymic tumors [10,15]. Although MG is not commonly observed in patients with thymic carcinoma, it can still be considered as a paraneoplastic Although the underlying mechanisms that link MG to a better prognosis are unclear, the following theories may contribute.…”
Section: Discussionmentioning
confidence: 97%
“…Current incidence rates vary from 9 to 21 per million, and prevalence rates are between 50 and 125 per million worldwide [13]. Approximately 10-12 % of patients with MG have thymomas, whereas 30 % of thymomas are accompanied by MG [14,15]. Few studies report the coexistence of MG and thymic carcinoma, however, and the reported incidence varies dramatically, from 3.8 % to 32.5 % [2,4,16,17].…”
Section: Introductionmentioning
confidence: 93%
“…The first and most important is the rarity of thymic carcinoma [2,14]. The uncommonness of the malignancy makes it difficult to collect sufficient data to analyze the outcomes of lymph node dissection and suggest appropriate treatment recommendations.…”
Section: Commentmentioning
confidence: 99%
“…The stage of thymic disease was classified according to the clinical and pathological classification by Masaoka et al as following: (stage I) encapsulated thymoma with no findings of microscopic or gross capsular invasion; (stage II) microscopic transcapsular invasion or gross tumor growth into the mediastinal fat or pleura; (stage III) invasion of pericardium, great vessels, or lung; (stage IVa) pleural or pericardial dissemination through direct extension or drop metastasis; and (stage IVb) lymphatic or hematogenous metastases [6]. For patients with surgical excision, the stage was determinated by operative and pathological findings.…”
Section: Clinical Stagementioning
confidence: 99%
“…However, the results of 18 FDG-PET imaging in thymic pathology are frequently conflicting [4][5][6][7], and it remains an expensive and complicated procedure, performed with tracers and imaging equipment available at a limited number of sites in Italy.…”
Section: Introductionmentioning
confidence: 98%